Operative Time Predicts Long-Term Abdominal Morbidity and Complication Requiring Treatment after DIEP Flap Breast Reconstruction - Wen, Y. Edward; Steppe, Cyrus; Teotia, Sumeet S.; Haddock, Nicholas T. (Journal of Reconstructive Microsurgery, 2023)
Background The relationship between skin-to-skin operative time and long-term complications, as well as complications requiring treatment, after deep inferior epigastric perforator (DIEP) flap breast reconstructions has not been thoroughly investigated. The study objective was to evaluate if operative time would independently prognosticate the type and number of treated complications, as well as long-term abdominal morbidity.Methods Patients who underwent bilateral DIEP flaps from 2010 to 2021 by two senior surgeons with standardized surgical and postoperative protocols were retrospectively reviewed. Inclusion required at least 1 year of postoperative follow-up. Extensive multivariable regression analyses were utilized to adjust for potential confounders, including measures of intraoperative complexity.Results Three hundred thirty-five patients were entered into multivariable analyses. After risk adjustment, there was a significant increase in the risk of all treated complications per hour. Each hour of operation increased risk of complications requiring extended hospital stay for treatment by 25%, flap-site complications requiring readmission treatment by 24%, and flap-site complications requiring extended hospital stay for treatment by 26% (all p < 0.0001). Long-term abdominal morbidity (abdominal bulge) increased by 25% per hour of operative time (p < 0.0001). The number of complications requiring treatment, abdominal donor-site complications, and complications requiring extended hospital stay for treatment had statistically significant linear relationships with the duration of surgery (all p < 0.05).Conclusion Operative time predicts long-term abdominal morbidity and complications requiring treatment, especially impacting the odds of developing abdominal bulges and complications requiring extended hospital stay for treatment or readmission treatment. This study emphasizes the importance of reducing operative time to improve DIEP flap breast reconstruction outcomes.
Keywords: DIEP flap breast reconstruction; operative time; long-term morbidity; complication treatment